2019
DOI: 10.5114/aoms.2019.90335
|View full text |Cite
|
Sign up to set email alerts
|

The effects of hepatic ischemia/reperfusion injury on postoperative cognitive function in aged rats

Abstract: Introduction: Hepatic ischemia/reperfusion injury (I/R) is a significant source of morbidity and mortality after liver surgery. The aim of this study was to investigate the effect of hepatic I/R injury on the hippocampus in rats with postoperative cognitive dysfunction (POCD). Material and methods: Adult male Sprague-Dawley rats (n = 160, age: 20-25 months, weight: 300-350 g) received I/R surgery with ischemia for 20 minutes, 30 minutes, and 40 minutes in different groups. Behavior tests of the Morris water ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Previous research, including our team's previous work, has confirmed that HIRI can induce cognitive dysfunction in mice 30–32 . The occurrence of this cognitive impairment is closely related to gut microbiota and hippocampal lipid metabolism.…”
Section: Introductionmentioning
confidence: 51%
See 1 more Smart Citation
“…Previous research, including our team's previous work, has confirmed that HIRI can induce cognitive dysfunction in mice 30–32 . The occurrence of this cognitive impairment is closely related to gut microbiota and hippocampal lipid metabolism.…”
Section: Introductionmentioning
confidence: 51%
“…29 Previous research, including our team's previous work, has confirmed that HIRI can induce cognitive dysfunction in mice. [30][31][32] The occurrence of this cognitive impairment is closely related to gut microbiota and hippocampal lipid metabolism. To further explore the mechanisms underlying hepatic ischemia-reperfusion-induced cognitive dysfunction, our research group employed techniques including gut microbiota transplantation and LC/MS short-chain fatty acid detection to investigate changes in the hippocampus of mice subjected to HIRI.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, hepatic ischemia-reperfusion injury (I/R) occurring during the perioperative period also has adverse effects on cognition (He et al, 2023). Many basic research studies have reported cognitive impairments in experimental animals after experiencing hepatic I/R injury (Wu et al, 2019;Wang et al, 2022).…”
Section: Liver Disease-related Mild Cognitive Impairment Statusmentioning
confidence: 99%
“…Additionally, these deficits contribute to reduced long-term quality of life and increased economic burden [9]. Growing evidence suggests that I/R in peripheral organs, including the liver [10][11][12], kidneys [13,14], intestines [15,16], and limbs [17], is a risk factor for cognitive impairment. Cardiac I/R has been specifically identified as an important contributor to cognitive dysfunction following cardiac surgery [18].…”
Section: Introductionmentioning
confidence: 99%